Long range energy efficient wireless sensor system : doctoral thesis - Purković, Dalibor (D. Purković ; Fakultet elektrotehnike i računarstva, 2019)
Energy consumption has become one of the main parameters in evaluating sensor systems in the IoT market. The long range sensor systems which are discussed in this dissertation are not an exception. Their application in the outdoor environment makes them an ideal candidate for combining energy harvesting mechanisms with low power features. As it is discovered, using just the low power electric components is not enough to ensure energy efficiency. Techniques and mechanisms for harvesting and saving energy had to be investigated and developed in order to successfully realize an energy efficient sensor system. The approach used was to build an entire sensor system from scratch, with careful selection of the main hardware components, and a deeper analysis of their behaviour and energy consumption for different temperatures, humidity and supply voltages. The concept of having one developed Printed Circuit Board (PCB), which is used in both the transmitter and receiver side, resulted in the development of two different modules which share same hardware components. Based on the required application, these modules can be assembled as either a Sensor module or a Data logger module. Furthermore, a unique, low power, energy efficient communication protocol is developed and described. A communication protocol optimizes the way the information is collected from the environment, packed and transmitted over long distances with minimum needed energy. It is designed specifically for energy constrained sensor modules which rely on energy harvesting. Gathered information is transmitted in a form of two different packet types called Teach-in and Data telegrams, respectively. A detailed structure of these packets and the energy required for transmission is explained together with a deeper analysis of the protocol’s physical layer (PHY). In addition, big potential of the developed sensor system for mass market is demonstrated, as a result of the many proposed solutions that have been tested and implemented in fully developed functioning prototypes already running in different field installations. Keywords: sensor module, data logger module, low power, long range, wireless communication, energy harvesting, supercapacitor, teach-in telegram, data telegram, unidirectional communication, bidirectional communication, communication protocol, LPWAN.